2005
DOI: 10.1111/j.1532-5415.2005.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Alzheimer's Disease: Natural Course and Temporal Relation to Function and Cognitive Status

Abstract: Depressive symptoms are common in AD, but their prevalence decreases over time. Examination of the temporal relationship between depressive symptoms and risk factors suggests that decline in function but not in cognition precedes the first episode of depressive symptoms in patients with probable AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
83
4
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 45 publications
13
83
4
6
Order By: Relevance
“…There seems to be an increase in symptoms as cognitive performance levels drop from average to moderate and a decrease in symptoms as cognitive functioning declines to the level of poor cognitive functioning or elderly people are diagnosed with AD. This decline was also found in earlier research [8,16,23] , which investigated depressive symptoms in AD patients. The researchers suggested that depression becomes less common as dementia and cognitive decline become more severe.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…There seems to be an increase in symptoms as cognitive performance levels drop from average to moderate and a decrease in symptoms as cognitive functioning declines to the level of poor cognitive functioning or elderly people are diagnosed with AD. This decline was also found in earlier research [8,16,23] , which investigated depressive symptoms in AD patients. The researchers suggested that depression becomes less common as dementia and cognitive decline become more severe.…”
Section: Discussionsupporting
confidence: 55%
“…In the investigation of depressive symptomatology in AD various conclusions were also drawn. Some researchers found depressive symptoms were not related to cognitive status in AD [19,20] , while other researchers found depression to be common in the early phase of AD, and then decreased over time [8,16,[21][22][23] . Overall, there does not seem to be any consensus on whether and if so, how symptoms of anxiety and depression are related to the phase of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…First, depressive symptoms did not increase with the onset of MCI and slightly decreased after dementia onset. Although this is not consistent with prior reports of a very slight increase in depressive symptoms before dementia onset, 13,14 it is consistent with reports of stable 14 or declining 36 depressive symptoms after dementia onset and the lack of an association of cognitive level [37][38][39] and cognitive change 40 with change in depressive symptoms. Second, neither level of depressive symptoms nor change in symptoms over time was related to common neuropathologic lesions associated with cognitive decline and dementia.…”
Section: Model B)contrasting
confidence: 44%
“…Consistent with this idea, longitudinal studies of patients with AD identified in medical settings and followed longer than the present study suggest that depressive symptoms may eventually decrease in the disease. 30,31 The relation of depression to the pathologic features of AD has been difficult to establish. In a small study of persons without dementia, depression was associated with elevated cortical uptake of Pittsburgh Compound B, suggesting elevated ␀-amyloid.…”
Section: Discussionmentioning
confidence: 99%